Peroxisome proliferator‐activated receptor‐γ signalling protects hair follicle stem cells from chemotherapy‐induced apoptosis and epithelial–mesenchymal transition. (24th November 2021) - Piccini, I.; Brunken, L.; Chéret, J.; Ghatak, S.; Ramot, Y.; Alam, M.; Purba, T.S.; Hardman, J.; Erdmann, H.; Jimenez, F.; Paus, R.; Bertolini, M.
Summary: Background: Permanent chemotherapy‐induced alopecia (pCIA), for which preventive interventions remain limited, can manifest with scarring. While the underlying pathomechanisms of pCIA are unclear, depletion of epithelial hair follicle (HF) stem cells (eHFSCs) is likely to play a role. Objectives: To explore the hypothesis that, besides apoptosis, eHFSCs undergo pathological epithelial–mesenchymal transition (EMT) in pCIA, thus explaining the scarring phenotype. Furthermore, we tested whether a peroxisome proliferator‐activated receptor (PPAR)‐γ modulator could prevent pCIA‐associated pathomechanisms. Methods: Organ‐cultured human scalp HFs were treated with the cyclophosphamide metabolite 4‐hydroperoxycyclophosphamide (4‐HC). Additionally, HFs were pretreated with the agonistic PPAR‐γ modulator N ‐acetyl‐GED‐0507‐34‐Levo (NAGED), which has previously been shown to promote K15 expression and antagonize EMT in eHFSCs. Results: In accordance with anticipated hair bulb cytotoxicity, dystrophy and catagen induction, 4‐HC promoted apoptosis along with increased p53 expression, DNA damage and pathological EMT in keratin 15 + (K15) eHFSCs, as evidenced by decreased E‐cadherin expression and the appearance of fibronectin + and vimentin + cells in the hair bulge. Pretreatment with NAGED protected against 4‐HC‐induced hair bulb cytotoxicity/dystrophy, and apoptosis, p53 upregulation and EMT in the bulge, thereby significantly preventing depletion of K15 + human eHFSCs ex vivo . Conclusions: Since a key cyclophosphamide metabolite alone suffices to damage and deplete human scalp eHFSCs by promoting apoptosis, DNA damage and EMT ex vivo, strategies to prevent pCIA need to target these pathomechanisms. Given the ability of NAGED to prevent chemotherapy‐induced eHFSCs damage ex vivo, our study introduces the stimulation of PPAR‐γ signalling as a novel intervention strategy for the prevention of pCIA. Abstract : What is already known about this topic? Chemotherapy can lead to permanent hair loss, which can manifest as scarring alopecia. Unfortunately, the pathomechanism of this phenomenon is unknown, and efficient preventive interventions are lacking. What does this study add? Repeated treatment of organ‐cultured human hair follicles (HFs) with 4‐hydroperoxycyclophosphamide (4‐HC) led not only to expected dystrophic changes in the bulb, but also resulted in DNA damage, apoptosis and pathological epithelial–mesenchymal transition (EMT) of epithelial HF stem cells (eHFSCs). Pretreatment with a peroxisome proliferator‐activated receptor (PPAR)‐γ modulator hindered 4‐HC‐induced hair bulb cytotoxicity/dystrophy, and protected K15 + human eHFSCs from apoptosis and EMT, thereby significantly preventing their depletion ex vivo . What is the translational message? Stimulation of PPAR‐γ signalling is a promising novel intervention strategy for the prevention of permanent chemotherapy‐induced alopecia. Linked Comment: K. Natsuga. Br J Dermatol 2022; 186:14–15 . Plain language summary available online